Teaching Strategies Among Teachers of Social Studies: A Basis for an Enhanced Program - Barrientos, Floi Daniel C. (International Journal on Integrated Education, 2025)
This study aimed to determine the teaching strategies implemented by Grade 10 social studies teachers in public junior high schools in Cabuyao City, Laguna, with the primary goal to evaluate the effectiveness of these materials and create a program for enhancement in social studies education. Social Studies is a key subject in bringing up competent, active, informed citizens, through which students can examine historical, social, and political issues. This research focuses on the impact of using different teaching strategies on student engagement and learning outcomes regarding issues like the accessibility of teaching materials, teacher training, and institutional support. The research was conducted as a quantitative survey, and structured questionnaires were utilized to gather data from 47 Grade 10 social studies teachers. The respondents of the questionnaires were asked to provide information about their teaching strategies, available resources, and the support they get from their institutions. The findings show that most teachers apply interactive lectures, multimedia resources, and inquiry-based learning strategies when they want to engage students. A robust positive correlation was found between teachers' factors and their teaching strategies. The study argues the need for a skills promotion program., irrespective of the mix of the various teaching strategies in the classroom, the teacher's professional development, the optimal use of resources, and collaborative in-class learning activities. The study also recommends that administrators consider the continuous training of teachers and ensure that the resources for teaching are available and that policies that support the practice of innovative teaching are implemented. This survey is designed to pave the way for improving Social Studies Education in Cabuyao City and other similar areas.